Misperceptions of income distributions: Cross-country evidence from a randomized survey experiment - Elisabeth Bublitz (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2016)
This paper investigates whether the individual misperception of income distributions helps explain why, opposite to Meltzer and Richard (1981), higher initial inequality levels do not correlate positively with redistribution. I conduct a representative survey experiment in Brazil, France, Germany, Russia, Spain, and the United States, providing a personalized information treatment on the income distribution to a randomly chosen subsample. Most respondents misperceive their own position in the income distribution. These biases differ by country and the true income position. Misperceptions of the median income relate negatively to misperceived income positions, showing evidence for biased reference points. Correcting misperceptions slightly shifts the demand towards less redistribution in Germany and Russia which appears to be driven by respondents with a negative position bias. Apart from Spain and the US, treatment reactions lead to a convergence of the demand for redistribution across countries. The treatment also alters trust levels in government and beliefs about the importance of luck but not equally across bias types.
Keywords: D31; D63; H20; 330; income distribution; biased perceptions; inequality; survey experiment